A Systematic Review of Psychological Distress that Occurs During the Treatment of Tuberculosis - Sari, Gevi Melliya; Amin, Muhammad; Hidayati, Laily (International Journal of Psychosocial Rehabilitation, 2020)
Compliance with treatment is the key to the success of the DOTS program in patients with tuberculosis. Psychological problems are one of the factors that can result in non-compliance of patients following the DOTS treatment regimen. The purpose of this review is to explain the psychological problems that can arise in tuberculosis patients following the treatment program. This study used a systematic review with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). A search used the following data sources: Scopus, Science Direct, Pubmed and ProQuest. The total articles found were 1042 articles, the articles used totaled 17. The article search was limited to the last 5 years (2015-2020), the English language as well as full-text articles. Keywords used were "Psychological Distress", "Emotional Distress", and "Tuberculosis". The population included were respondents aged> 18 years who were undergoing a tuberculosis treatment regimen and had no previous history of mental disorders. The results show that the psychological disorders that may arise during the treatment of tuberculosis patients are depression, anxiety, loneliness, and psychological distress. Psychological disorders that arise can be associated with a decrease in quality of life and risk of multidrug-resistance and non-compliance with treatment. Conclusion: psychological distress occurs among tuberculosis patients and the most experienced of these among patients is depression. Interventions in tackling psychological disorders in tuberculosis patients are urgently needed to help patients improve in terms of completing tuberculosis treatment. The role of health workers in providing comprehensive nursing care and support from families is very helpful for patients in overcoming their psychological problems.